621.512 IMPROVING THE DESIGN OF WATER SPRAY NOZZLES IN COOLING TOWERS. - Pardayeva, Shahlo; Kayumov, Umidjon; Djurayev, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The operation of enterprises in the industrial complex is accompanied by the release of a large amount of heat from technological processes in the operating equipment, which must be removed to maintain the operating mode and the given rate of production. In industry and energy, recycled water cooled in cooling towers is used to condense exhaust steam and gaseous products, cool liquid products, as well as equipment and mechanisms in order to protect them from rapid destruction under the influence of high temperatures. The performance of technological equipment, the quality and cost of manufactured products, and the specific consumption of raw materials, fuel and electricity depend on the efficiency of cooling towers. Today, removing low-grade heat from industrial devices using cooling towers is the cheapest way, allowing you to save at least 95% of fresh water from the network. As can be seen from the above, in water cooling devices it is mainly related to the improvement and development of new types of irrigation nozzles and the general design of cooling towers.